PEMANFAATAN ECOBRICK SEBAGAI MEDIA KREATIVITAS DI KELURAHAN TANJUNG, KOTA BIMA - Agustiansyah, Muhammad Rizki; Rousanfikr, Sava Arcadia; Maulinda, Ade Azahra; Hening, Beta Tiva Ratu; Putri, Andi Nirmala; Az-Zahra, Annisa; Azmi, Muhammad; Puspita, Intan Imda; Hamdani, Muhammad Ananda Rizki; Rosmaliati, Rosmaliati (Universitas Mataram, 2024)
The problem of plastic waste is a serious issue in Indonesia, especially in Tanjung Village, Bima City, where waste management is still less than optimal. One solution implemented is the use of Ecobrick, a plastic waste management technique by filling used bottles with plastic until they are solid and hard. This program involves socialization and training at SDN 29 Tanjung and SMPN 13 Bima City, where students are taught how to process plastic waste into products with economic value such as furniture. The results of this program show that Ecobrick is effective in reducing the volume of plastic waste while increasing public awareness of the importance of waste management. The use of Ecobrick not only helps maintain environmental cleanliness but also provides economic benefits and has the potential to reduce negative environmental impacts such as coastal abrasion. It is hoped that this program can be the first step in forming new habits in the community related to waste management.